-14+3p+30=14p+28+p

Simple and best practice solution for -14+3p+30=14p+28+p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+3p+30=14p+28+p equation:


Simplifying
-14 + 3p + 30 = 14p + 28 + p

Reorder the terms:
-14 + 30 + 3p = 14p + 28 + p

Combine like terms: -14 + 30 = 16
16 + 3p = 14p + 28 + p

Reorder the terms:
16 + 3p = 28 + 14p + p

Combine like terms: 14p + p = 15p
16 + 3p = 28 + 15p

Solving
16 + 3p = 28 + 15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-15p' to each side of the equation.
16 + 3p + -15p = 28 + 15p + -15p

Combine like terms: 3p + -15p = -12p
16 + -12p = 28 + 15p + -15p

Combine like terms: 15p + -15p = 0
16 + -12p = 28 + 0
16 + -12p = 28

Add '-16' to each side of the equation.
16 + -16 + -12p = 28 + -16

Combine like terms: 16 + -16 = 0
0 + -12p = 28 + -16
-12p = 28 + -16

Combine like terms: 28 + -16 = 12
-12p = 12

Divide each side by '-12'.
p = -1

Simplifying
p = -1

See similar equations:

| 2b-7(5+4b)=15-b | | 16=-2x-20 | | 20x+80y=13 | | 7(-1-b)=-8b-12 | | 12p+3-9p=12-6p | | 6x-(12-x)=10(x+6)-7 | | -5-15m+1=14m-32-m | | 3b-3-12b-4= | | -58+23=-8x+15x | | 5+8b=3b+5(5b+5) | | (2x-6)5+2((3-2x)3+(7x-18))=8+3 | | 2m+18=16-4m-28 | | -5.4=1.3+x | | -10+2x=14 | | 1.50b^2-24b-24=0 | | 6(2p-6)=7p+4 | | 4y(y-7)=2y-38 | | 6x-4-3x=-2x+7-1 | | 2n-25=-3(-5n+4) | | (x^2)-6x=24 | | s/5=42 | | 3x=2x+1.5 | | 2d+3s=21 | | 8y*48=-22 | | 3m=m-2 | | 7p-2=2p+3p+12 | | (200x^2)-9000x+99072=0 | | 5-(n-4)=3(n++2) | | 8x+4x=4x-16 | | n+1-1-15=3n-1 | | p-1+6=5-3p | | 86-(21x-(17x+25))=16x-449 |

Equations solver categories